Tribasodes kamedai Nomura is not a strictly cavernicolous species (Coleoptera: Staphylinidae: Pselaphinae) - Jałoszyński, Paweł; Nomura, Shûhei; Tokushige, Norihide (Zootaxa, 2024)
Tribasodes kamedai Nomura, 2012 was described based on specimens collected in a limestone cave in Okinawa-jima Island. We demonstrate that this species is not a strict troglobite, but presumably a trogloxene, as it was recently collected in new localities from forest leaf litter and hollow trees. Tribasodes kamedai is redescribed in detail, with the first illustrations of female genitalia, notes on interspecific variability, and new distributional records.